ANALISIS PENERAPAN SISTEM PENCATATAN DAN PELAPORAN TERPADU PUSKESMAS (SP2TP) PUSKESMAS SUKAMERINDU KOTA BENGKULU - Rahman Ade Ghaniy; S. Efendi; Susilo Wulan; Deni Triyanto (Dian Nuswantoro Semarang, 2020)
The Integrated System for Recording and Reporting (ISRR) Sukamerindu Public Health Center of Bengkulu there are several problems, namely the provision of inaccurate data / information, reporting that is often not timely and there is no standard mechanism. This study aims to analyze the application of ISRR from the aspect of input (human resources, funding, equipment), process (recording, reporting), and output (presentation of data & information, dissemination, utilization). The research method is qualitative research with a phenomenological approach through in-depth interviews with 3 key informants and 6 ordinary informants. Data processed by the Content analysis method and SWOT analysis to determine the formulation of strategies for the problems found. The results showed that ISRR Sukamerindu Public Health Center had not run optimally, this was due to lack of human resources, lack of coordination between data managers and program holders, lack of equipment, manual recording and recapitulation with personal laptops, there were still delays in sending reports and data became less accurate. The data presentation is more complete, the distribution is only to the Bengkulu Department of Health, and the data is used for evaluation for health policy stakeholders. To improve the performance of the implementation of ISRR Sukamerindu Public Health Center researchers suggested that the Bengkulu Department of Health further enhance its collaboration with Public Health Centers by optimizing communication and conducting planned and continuous training to get skilled and professional human resources in ISRR management.Keywords: Analysis, Public Health Center, Recording, Reporting, Syste